Zatoichi the outlaw [videorecording (DVD)] - Yamamoto, Satsuo, 1910-1983; Katsu, Shintarō, 1931-1997; Mikuni, Rentarō, 1923-2013; Nishimura, Kō; Shimozawa, Kan, 1892-1968 (AnimEigo, 2003)
In this 16th movie of Zatoichi the blind swordsman, he finds himself involved with a gambling house who plot to enlist him to eliminate a rival.